Structural Toughness Enhancement Method for Material Extrusion-Based 3D-Printed Model: A Rigid Shell-Flexible Infill Composite Structure - Chen Wang; Han-yi Huang; Xiaowen Wang (BioResources)
This study addressed the problem of poor structural toughness of material extrusion-based (MEX) 3D printing polylactic acid (PLA) models and expanded the application of 3D printing technology. A new structural toughness enhancement method was proposed to improve the structural toughness of MEX 3D-printed models by constructing a rigid shell-flexible infill composite structure. Rectangular specimens were designed using SolidWorks software, and the structural toughness of the rigid specimens and rigid shell-flexible infill specimens were tested using three-point bending test and Charpy impact test. The deflection, bending strain energy, and impact strength of the rigid shell-flexible infill specimens were larger than those of the rigid specimens. The enhancement percentages were 103%, 306% and 293%, respectively, indicating that the rigid shell-flexible infill specimens had better structural toughness. In contrast to the conventional material modification methods, the structural toughness enhancement method proposed in this study can maintain the strength and stiffness of 3D-printed models while improving their impact resistance and ductility. The products have unique application value in the fields of smart packaging, sports protective gears, and consumer electronic products.